Seasonal variation of airborne fungal diversity and community structure in urban outdoor environments in Tianjin, China - Nageen, Yumna; Wang, Xiao; Pecoraro, Lorenzo (Frontiers in Microbiology, 2023)
Airborne fungi are ubiquitous in human living environments and may be a source of respiratory problems, allergies, and other health issues. A 12 months study was performed to investigate the diversity, concentration and community structure of culturable airborne fungi in different outdoor environments of Tianjin City, using an HAS-100B air sampler. A total of 1015 fungal strains belonging to 175 species and 82 genera of Ascomycota 92.5%, Basidiomycota 7%, and Mucoromycota 0.3% were isolated and identified using morphological and molecular analysis. The most abundant fungal genera were Alternaria 35%, Cladosporium 18%, Penicillium 5.6%, Talaromyces 3.9%, Didymella 3%, and Aspergillus 2.8%, while the most frequently occurring species were A. alternata (24.7%), C. cladosporioides (11%), A. tenuissima (5.3%), P. oxalicum (4.53%), and T. funiculosus (2.66%). The fungal concentration ranged from 0 to 340 CFU/m3 during the whole study. Environmental factors, including temperature, relative humidity, wind speed, and air pressure exerted a varying effect on the presence and concentration of different fungal taxa. The four analyzed seasons showed significantly different airborne fungal communities, which were more strongly influenced by air temperature and relative humidity in spring and summer, whereas wind speed and air pressure had a stronger effect in autumn and winter. Fungal communities from green and busy sites did not show significant differences over the four analyzed seasons, which may be due to the effect of the surrounding environments characterized by high human activities on the air of the relatively small parks present in Tianjin. The present study provided valuable information on the seasonal dynamics and the environmental factors shaping the diversity and concentration of the analyzed outdoor airborne fungal communities, which can be of help for air quality monitoring, microbial contamination control, and health risk assessment in urban environments.